Pembuatan dan Karakterisasi Dissolving Pulp Serat Panjang dari Bambu Duri (Bambusa blumeana) - Chandra Apriana Purwita; Susi Sugesty (JURNAL SELULOSA, 2018)
Preparation and Characterization of Long Fiber Dissolving Pulp from Spiny Bamboo (Bambusa blumeana)The need for long fiber dissolving pulp in Indonesia can only be met from imports. Bamboo is a nonwood plant and known as source of long fiber. This research aims to study the potential of spiny bamboo to be used as raw material for producing long fiber dissolving pulp. This research was conducted using two different types of raw materials preparation to produce bamboo chip and decorticated bamboo. The pulping process is carried out by pre-hydrolysis kraft and bleaching performed with two different bleaching sequences, i.e Do ED1 D2 and Do EpD1 D2 . Based on the experimental results, spiny bamboo has good potential to be used as raw material for dissolving pulp. Spiny bamboo belongs to long fibers with an average fiber length of 2.46 mm. The dissolving quality depends on the preparation of the raw material and the bleaching sequence. The yield of spiny bamboo dissolving pulp ranged from 37.97 - 40.76% with alpha cellulose content of 94.88 - 98.67%, and viscosity of 16.43 - 25.75 cP. Decorticated bamboo with bleaching sequence of Do EpD1 D2 produced the highest quality of dissolving pulp with the highest brightness and alpha cellulose were 89.61% ISO and 98.67%, respectively.AbstrakKebutuhan dissolving pulp serat panjang di Indonesia hanya dapat dipenuhi melalui impor. Bambu adalah tanaman nonkayu dan dikenal sebagai sumber serat panjang. Penelitian ini bertujuan untuk mempelajari potensi bambu duri untuk dijadikan bahan baku pembuatan dissolving pulp serat panjang. Penelitian ini dilakukan dengan dua jenis persiapan bahan baku yang berbeda untuk menghasilkan serpih bambu dan bambu dekortikasi. Proses pemasakan dilakukan dengan proses pra-hidrolisis kraft dan pemutihan dilakukan dengan dua urutan pemutihan yang berbeda, yaitu  DoED1D2 dan DoEpD1D2. Berdasarkan hasil penelitian, bambu duri memiliki potensi yang baik untuk digunakan sebagai bahan baku pembuatan dissolving pulp. Bambu duri tergolong serat panjang dengan panjang serat rata-rata 2,46 mm. Kualitas dissolving pup yang dihasilkan tergantung dari persiapan bahan baku dan urutan pemutihan. Rendemen dissolving pulp bambu duri berkisar 37,97 - 40,76%, dengan kandungan selulosa alfa 94,88 - 98,67%, dan viskositas 16,43 - 25,75 cP. Bambu dekortikasi dengan urutan pemutihan DoEpD1D2 menghasilkan dissolving pulp paling unggul dengan derajat cerah dan selulosa alfa tertinggi berturut-turut 89,61 %ISO dan 98,67%.Kata kunci: dissolving pulp, bambu duri (Bambusa blumeana), serpih bambu, bambu dekortikasi, prahidrolisis kraft